A NdFeB sintering method conducive to decarbonization

By adopting a multi-stage heating and insulation platform during the NdFeB sintering process, and using alternate insulation sintering with inert gas pressure difference, the problem of difficult carbon elements in NdFeB sintering is solved, and the magnetic properties of the magnet are improved.

CN119889855BActive Publication Date: 2025-06-10NINGBO YUNSHENG CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510371001.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-06-10
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

During the sintering process of neodymium iron boron, it is difficult to effectively remove carbon elements, which affects the performance of the matrix and the smooth flow of grain boundary diffusion channels.

Method used

A multi-stage heating and insulation platform is adopted, and inert gas is introduced and extracted during insulation to form an inert gas pressure difference, which forms alternate insulation and sintering to reduce the carbon content of the blank.

Benefits of technology

Through this method, the carbon content inside the blank is effectively reduced, the smoothness of the grain boundary diffusion channel is improved, and the magnetic properties of the neodymium iron boron magnet are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889855B_ABST
    Figure CN119889855B_ABST
Patent Text Reader

Abstract

The present invention discloses a sintering method for neodymium iron boron that helps with decarburization. The chemical formula of the neodymium iron boron magnet is R X1 T (100‑X1‑X2‑X3‑X4) M X3 A X4 B X2 , and the main steps are as follows: Mix the neodymium iron boron raw materials in proportion, melt them into an alloy liquid, cast them into sheets, grind them into powder, and load them into a tank with inert gas protection, and stir well. Compact and orient the powder blank, use vacuum packaging, isostatic pressing with water, and carry out sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating form, and an inert gas pressure difference is formed by introducing and extracting inert gas during heat preservation for alternative heat preservation sintering. After sintering is completed, cool it to below 100°C, take the central part of the sintered magnet, and test the nitrogen, oxygen, and carbon contents in the blank. The present invention provides a sintering method for neodymium iron boron that helps with decarburization and removes carbon elements during the sintering process of neodymium iron boron by using the sintering process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of NdFeB production, and specifically to a sintering method for NdFeB that helps with decarburization. Background Art

[0002] With the rapid development of the application fields of rare earth permanent magnets, the demand for high-performance and low-cost NdFeB permanent magnets has increased rapidly. Therefore, improving the magnetic properties of NdFeB and developing high-performance sintered NdFeB have become the primary technical problems to be solved. One of the main applications of rare earth permanent magnet materials is to manufacture various permanent magnet motors. Compared with traditional motors, permanent magnet motors have the characteristics of light weight, small size, high efficiency, energy saving, and strong reliability. Sintered NdFeB permanent magnets are small in volume and high in performance, which can well reduce the mass of motors and improve the efficiency of motors, and are more suitable for the miniaturization and lightweight of automobiles.

[0003] Currently, the most effective method to increase the coercivity (H CJ c) is to use heavy rare earth elements terbium (Tb) and dysprosium (Dy) to replace neodymium (Nd) elements in the alloy to form (Nd,Tb) 2 Fe 14 B or (Nd,Dy) 2 Fe 14 B. Among them, grain boundary diffusion technology and grain boundary doping technology are effective ways to prepare high coercivity without heavy rare earth or with low heavy rare earth.

[0004] Since the grain boundary diffusion technology was proposed, it has attracted wide attention in the industry and has been rapidly industrialized in recent years. In actual industrial production, using the grain boundary diffusion process can reduce the consumption of heavy rare earth by more than 50%. However, the requirements for the blank matrix in the grain boundary diffusion process are increased, and the lower the carbon, oxygen, and nitrogen content in the matrix, the easier it is to ensure the smooth passage of the grain boundary diffusion.

[0005] For the matrix of grain boundary diffusion, in the powder making and forming stages, the introduction of carbon elements is deliberately reduced as much as possible, such as reducing the use of lubricants and surface modifiers, etc. However, in order to ensure the flow and formability of the powder, it is inevitable to add antioxidant agents, fluid energy mill protective agents, etc. Therefore, the introduction of this part of the inevitable carbon elements affects the matrix performance and also affects the smooth passage of the grain boundary diffusion. Summary of the Invention

[0006] The technical problem to be solved by the present invention is: to provide a sintering method for NdFeB that can remove carbon elements during the sintering process of NdFeB by using the sintering process.

[0007] The technical solution adopted by the present invention to solve the above problems is: a sintering method for NdFeB that helps with decarburization, and the chemical formula of the NdFeB magnet is R X1 T (100-X1-X2-X3-X4) M X3 AX4 B X2 During sintering, a multi-stage heating and insulation platform is used, and during insulation, inert gas is introduced and extracted to form an inert gas pressure difference for alternating insulation sintering, thereby reducing the carbon content inside the blank. The steps are as follows:

[0008] S1: Mix NdFeB raw materials in proportion;

[0009] S2: Smelting the NdFeB raw materials into alloy liquid;

[0010] S3: Casting the alloy liquid into casting sheets;

[0011] S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly;

[0012] S5: Pressing the powder into a green compact and orienting the green compact;

[0013] S6: vacuum packaging;

[0014] S7: performing water isostatic pressing;

[0015] S8: Sintering and film stripping are performed. The sintering adopts a multi-stage heat preservation and temperature rise form, and inert gas is introduced and extracted during the heat preservation to form an inert gas pressure difference for alternating heat preservation and sintering;

[0016] S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C;

[0017] S10: Take the center part of the sintered magnet and test the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and test the carbon content in the blank by high-frequency-infrared absorption method.

[0018] Compared with the prior art, the advantages of the present invention are: through step S8, during the sintering process, staged insulation is adopted to avoid the formation of a high-temperature reaction isolation layer, ensuring that the temperature inside and outside the blank is consistent, thereby ensuring that the diffusion channel is open; at the same time, the inert gas pressure difference in the insulation section is alternately adopted to promote the interaction between the organic gas and the inert gas, and then a vacuum pump is used to form a negative pressure to take away more carbides.

[0019] As an improvement of the present invention, in step S8, the following steps are included:

[0020] S8.1: Start heating from room temperature;

[0021] S8.2: Raise the temperature to 100°C~400°C;

[0022] S8.3: Keep warm for 1h~4h;

[0023] S8.4: Raise the temperature to 400°C~600°C;

[0024] S8.5: Insulate for 1 h to 4 h;

[0025] S8.6: Heat up to 600 °C to 900 °C;

[0026] S8.7: Insulate for 1 h to 4 h;

[0027] Through the above improvement, in the conventional sintered NdFeB material, the organic matters adsorbed on the surface of the blank, such as mold release agents, etc., can be gasified at 100 °C - 400 °C and discharged out of the blank along with the diffusion channels. Therefore, a long-time first preheating is carried out in S8.2 and S8.3; then, the temperature is raised again through steps S8.4 and S8.5. At this stage, the particle gaps in the blank are further reduced, and the hydrogen, carbon, and oxygen substances with strong binding between the powder particles escape; then, through steps S8.6 and S8.7, the temperature is raised to 600 °C to 900 °C, and a liquid phase begins to appear in the sintered NdFeB, the particles are rearranged, and the diffusion channels become narrower. This stage requires a longer time to reach the lowest temperature gradient inside and outside the blank, and eliminate the phenomenon that the channels are blocked due to more liquid phase at a higher temperature outside the blank, resulting in the inability of organic matters to be discharged.

[0028] As an improvement of the present invention, in steps S8.3, S8.5, and S8.7, the following steps are all included:

[0029] A1: After starting to insulate, fill with inert gas;

[0030] A2: After maintaining for a period of time, evacuate to vacuum;

[0031] A3: In a vacuum state, after maintaining for a period of time;

[0032] A4: Repeat steps A1 - A3 not less than twice;

[0033] Through the above improvement, during the sintering process, the carbon elements removed from the blank mainly exist in the form of direct volatilization or carbide gases. Therefore, through steps A1 - A4, the movement ability of the carbon and carbide gases in the volatile state can be enhanced, and sufficient diffusion time can be provided to enable them to quickly diffuse throughout the sintering equipment. Then, by filling with inert gas, the carbon and carbide gases in the volatile state are diluted, so that the carbon and carbide gases in the volatile state can be fully diffused into the inert gas. When evacuating to vacuum again, the difficulty of evacuating the carbon and carbide gases in the volatile state is reduced, thereby reducing the inhibitory effect of the carbon and carbide gases in the volatile state on the subsequent decarbonization reaction.

[0034] Through the above improvement, after step S8.7, there is also a step, S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, raise the sintering temperature to 1050 ± 50 °C, and the insulation duration is 4 - 15 hours. Through the above improvement, the blank is sintered and shaped.

[0035] As an improvement of the present invention, in step S9, after sintering is completed, high-purity inert gas is filled in for cooling to below 100°C. Through this improvement, after the blank is sintered and formed in a vacuum, by filling in high-purity inert gas, not only can the blank be rapidly cooled, but when cooled to below 100°C, it ensures that the sintered blank tends to a stable state and guarantees the sintering quality of the blank.

[0036] As an improvement of the present invention, after step S9, it further includes step S9.1: performing aging treatment on the sintered magnet. Through this improvement, the magnetic properties of the magnet are enhanced through aging treatment.

[0037] As an improvement of the present invention, in step S4, it includes step S4.1: adding a powder modifier with an addition ratio of 0.05wt% - 0.5wt% and performing sufficient stirring. Through this improvement, it has an anti-oxidation protection effect, isolating the magnetic powder from contact with air, significantly reducing the oxidation risk of neodymium-iron-boron powder before sintering; improving the powder fluidity, the lipophilic hydrocarbon chain structure of the modifier can reduce the force between powder particles, inhibit the agglomeration phenomenon, and make the powder easier to flow and uniformly fill the mold; enhancing flame retardancy and safety, in processing links such as jet mills, the modifier prevents the magnetic powder from burning accidents caused by friction or collision by reducing the surface activity of the powder; promoting magnetic field orientation, the lubricating effect of the modifier makes the magnetic powder particles more easily rotate and align in the magnetic field, thereby improving the remanence B r and the maximum magnetic energy product (BH) max 。

[0038] As an improvement of the present invention, in step S5, it includes step S5.1: spraying a release agent during the forming process. Through this improvement, it is convenient for the blank to be demolded after forming.

[0039] As an improvement of the present invention, it further includes the following steps:

[0040] S11: Processing the sintered magnet into a thin sheet and performing grain boundary diffusion;

[0041] S12: Testing the magnetic properties before and after diffusion with a magnetic tester. Through this improvement, grain boundary diffusion is performed on the sintered and formed magnet to further improve the magnetic properties of the magnet, and then the change in magnetic properties is measured. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 is a schematic diagram of the sintering curve and the pressure change curve of the sintering equipment of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0043] The embodiments of the present invention will be further described below with reference to the drawings.

[0044] A neodymium-iron-boron sintering method that helps with decarbonization, the chemical formula of the neodymium-iron-boron magnet is R X1 T (100-X1-X2-X3-X4) M X3 A X4 B X2 ;

[0045] where X1, X2, X3, and X4 are the mass percentages of the corresponding elements respectively;

[0046] R is selected from one or more of the rare earth elements, 28.5 wt% ≤ X1 ≤ 32.5 wt%;

[0047] T is selected from Fe and Co, the content of Co is 0 - 1.0 wt%, and the balance is Fe;

[0048] M is selected from one or more of Ti, Zr, and Nb, 0.1 wt% ≤ X3 ≤ 0.35 wt%;

[0049] A is selected from Cu, Ga, and Al, 0.0 wt% ≤ X4 ≤ 1.2 wt%;

[0050] B is B, the content is 0.88 wt% ≤ X2 ≤ 0.98 wt%;

[0051] During sintering, a multi-stage heating and holding platform is adopted, and inert gas is introduced and extracted during holding to form an alternating holding sintering with an inert gas pressure difference, thereby reducing the carbon content inside the blank. The steps are as follows:

[0052] S1: Mix the neodymium-iron-boron raw materials in proportion;

[0053] S2: Melt the neodymium-iron-boron raw materials into an alloy liquid;

[0054] S3: Cast the alloy liquid into cast sheets;

[0055] S4: Grind the cast sheets into powder, load them into a tank with inert gas protection, and stir well;

[0056] S4.1: Add a powder modifier, the addition ratio is 0.05 wt% - 0.5 wt%, and stir well;

[0057] S5: Press and orient the powder blank;

[0058] S5.1: Spray a release agent during the forming process;

[0059] S6: Adopt vacuum packaging;

[0060] S7: Perform hydrostatic pressing;

[0061] S8: Perform sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating mode, and an inert gas pressure difference is formed by introducing and extracting inert gas during heat preservation for alternative heat preservation sintering;

[0062] S8.1: Heat up from room temperature;

[0063] S8.2: Heat up to 100°C to 400°C;

[0064] S8.3: Keep warm for 1h to 4h;

[0065] S8.3.1: Fill with inert gas;

[0066] S8.3.2: After maintaining for a period of time, evacuate;

[0067] S8.3.3: In a vacuum state, after maintaining for a period of time;

[0068] S8.3.4: Repeat the steps of S8.3.1 - S8.3.3 no less than once;

[0069] S8.4: Heat up to 400°C to 600°C;

[0070] S8.5: Keep warm for 1h to 4h;

[0071] S8.5.1: Fill with inert gas;

[0072] S8.5.2: After maintaining for a period of time, evacuate;

[0073] S8.5.3: In a vacuum state, after maintaining for a period of time;

[0074] S8.5.4: Repeat the steps of S8.5.1 - S8.5.3 no less than once;

[0075] S8.6: Heat up to 600°C to 900°C;

[0076] S8.7: Keep warm for 1h to 4h;

[0077] S8.7.1: Fill with inert gas;

[0078] S8.7.2: After maintaining for a period of time, evacuate;

[0079] S8.7.3: In a vacuum state, after maintaining for a period of time;

[0080] S8.7.4: Repeat the steps of S8.7.1 - S8.7.3 no less than once;

[0081] S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, raise the sintering temperature to 1050 ± 50°C, and keep warm for 4 to 15 hours;

[0082] S9: After sintering is completed, charge high-purity inert gas and cool to below 100 °C;

[0083] S9.1: Perform aging treatment on the sintered magnet;

[0084] S10: Take the central part of the sintered magnet, use the pulsed infrared absorption method to test the nitrogen and oxygen content in the blank, and use the high-frequency infrared absorption method to test the carbon content in the blank;

[0085] S11: Process the sintered magnet into a thin sheet of 10 mm × 10 mm × 5 mm and perform grain boundary diffusion;

[0086] S12: Use a NIM62000 magnetic tester as the test equipment to test the magnetic properties before and after diffusion.

[0087] Example 1.1: The casting sheet formula is: (PrNd) 30%B 0.94%Ti 0.2%(Al+Cu+Ga) 0.35%Co 1%, and the rest is Fe.

[0088] The steps are as follows:

[0089] S1: Mix neodymium iron boron raw materials in proportion;

[0090] S2: Melt the neodymium iron boron raw materials into an alloy liquid;

[0091] S3: Cast the alloy liquid into a casting sheet;

[0092] S4: Grind the casting sheet into powder, put it into a tank with inert gas protection, and stir well;

[0093] S4.1: Add a powder modifier with an addition ratio of 0.1 wt% and stir well;

[0094] S5: Press and orient the powder blank;

[0095] S5.1: Spray a mold release agent during the molding process, with a weight ratio of 0.1 wt%;

[0096] S6: Adopt vacuum packaging;

[0097] S7: Perform hydrostatic isostatic pressing;

[0098] S8: Perform sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating form;

[0099] S8.1: Start heating from room temperature;

[0100] S8.2: Heat up to 200 °C;

[0101] S8.3: Keep warm for 2 h;

[0102] S8.3.1: Fill with inert gas, filling pressure 0.05 MPa;

[0103] S8.3.2: After maintaining for 30 min, evacuate the vacuum;

[0104] S8.3.3: Maintain for 30 min in a vacuum state;

[0105] S8.3.4: Repeat the steps of S8.3.1 - S8.3.3 once again;

[0106] S8.4: Heat up to 560 °C;

[0107] S8.5: Keep the temperature for 2 h;

[0108] S8.5.1: Fill with inert gas, filling pressure 0.05 MPa;

[0109] S8.5.2: After maintaining for 30 min, evacuate the vacuum;

[0110] S8.5.3: Maintain for 30 min in a vacuum state;

[0111] S8.5.4: Repeat the steps of S8.5.1 - S8.5.3 once again;

[0112] S8.6: Heat up to 820 °C;

[0113] S8.7: Keep the temperature for 3 h;

[0114] S8.7.1: Fill with inert gas, filling pressure 0.05 MPa;

[0115] S8.7.2: After maintaining for 30 min, evacuate the vacuum;

[0116] S8.7.3: Maintain for 30 min in a vacuum state;

[0117] S8.7.4: Repeat the steps of S8.7.1 - S8.7.3 twice;

[0118] S8.8: Evacuate the vacuum to a vacuum degree less than 10 -2 Pa, heat up the sintering temperature to 1082 °C, and keep the temperature for 7 h;

[0119] S9: After completing sintering, fill with high-purity inert gas and cool to below 100 °C;

[0120] S9.1: Then, through the secondary aging treatment process of maintaining at 900 °C for 2 - 3 h and 500 °C for 3 - 6 h, fill with high-purity inert gas and cool to below 100 °C;

[0121] S10: Take the central part of the sintered magnet, and use the pulse infrared absorption method to test the nitrogen and oxygen contents in the blank, and use the high-frequency infrared absorption method to test the carbon content in the blank;

[0122] S11: Process the sintered magnet into a thin slice of 10mm×10mm×5mm, and perform grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.62wt%;

[0123] S12: Use a NIM62000 magnetic tester as the test equipment to test the magnetic properties before and after diffusion.

[0124] Example 1.2: The casting sheet formula is: (PrNd)30%B0.94%Ti0.2%(Al+Cu+Ga)0.35%Co1%, and the rest is Fe.

[0125] The steps are as follows:

[0126] S1: Mix the neodymium iron boron raw materials in proportion;

[0127] S2: Melt the neodymium iron boron raw materials into alloy liquid;

[0128] S3: Cast the alloy liquid into casting sheets;

[0129] S4: Grind the casting sheets into powder, put them into a tank with inert gas protection, and stir well;

[0130] S4.1: Add a powder modifier, with an addition ratio of 0.1wt%, and stir well;

[0131] S5: Press and orient the powder blank;

[0132] S5.1: Spray a mold release agent during the forming process, with a weight ratio of 0.1wt%;

[0133] S6: Adopt vacuum packaging;

[0134] S7: Perform hydrostatic isostatic pressing;

[0135] S8: Perform sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating form;

[0136] S8.1: Start heating from room temperature;

[0137] S8.2: Heat up to 200°C;

[0138] S8.3: Keep warm for 3h;

[0139] S8.3.1: Fill in an inert gas, with a filling pressure of 0.05MPa;

[0140] S8.3.2: After maintaining for 30min, evacuate;

[0141] S8.3.3: Keep it in a vacuum state for 30 min;

[0142] S8.3.4: Repeat the steps of S8.3.1 - S8.3.3 twice;

[0143] S8.4: Heat up to 560 °C;

[0144] S8.5: Keep the temperature for 3 h;

[0145] S8.5.1: Fill with inert gas, and the filling pressure is 0.05 MPa;

[0146] S8.5.2: After keeping for 30 min, evacuate;

[0147] S8.5.3: Keep it in a vacuum state for 30 min;

[0148] S8.5.4: Repeat the steps of S8.5.1 - S8.5.3 twice;

[0149] S8.6: Heat up to 820 °C;

[0150] S8.7: Keep the temperature for 4 h;

[0151] S8.7.1: Fill with inert gas, and the filling pressure is 0.05 MPa;

[0152] S8.7.2: After keeping for 30 min, evacuate;

[0153] S8.7.3: Keep it in a vacuum state for 30 min;

[0154] S8.7.4: Repeat the steps of S8.7.1 - S8.7.3 three times;

[0155] S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, heat up the sintering temperature to 1082 °C, and keep the temperature for 7 h;

[0156] S9: After completing sintering, fill with high-purity inert gas and cool down to below 100 °C;

[0157] S9.1: Then, through a secondary aging treatment process of keeping at 900 °C for 2 - 3 h and 500 °C for 3 - 6 h, fill with high-purity inert gas and cool down to below 100 °C;

[0158] S10: Take the central part of the sintered magnet, and use the pulse infrared absorption method to test the nitrogen and oxygen contents in the blank, and use the high-frequency - infrared absorption method to test the carbon content in the blank;

[0159] S11: Process the sintered magnet into a thin sheet of 10 mm×10 mm×5 mm, and perform grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.62 wt%.

[0160] S12: Use a NIM62000 magnetic tester as the test equipment to test the magnetic properties before and after diffusion.

[0161] Comparative Example 1: The casting sheet formula is: (PrNd)30%B0.94%Ti0.2%(Al+Cu+Ga)0.35%Co1%, and the rest is Fe.

[0162] The steps are as follows:

[0163] S1: Mix the neodymium iron boron raw materials in proportion;

[0164] S2: Melt the neodymium iron boron raw materials into an alloy liquid;

[0165] S3: Cast the alloy liquid into a casting sheet;

[0166] S4: Grind the casting sheet into powder, put it into a tank with inert gas protection, and stir well;

[0167] S4.1: Add a powder modifier with an addition ratio of 0.1 wt%, and stir well;

[0168] S5: Press and orient the powder blank;

[0169] S5.1: Spray a release agent during the forming process, with a weight ratio of 0.1 wt%;

[0170] S6: Adopt vacuum packaging;

[0171] S7: Perform hydrostatic isostatic pressing;

[0172] S8: Perform sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating form;

[0173] S8.1: Start heating from room temperature;

[0174] S8.2: Heat up to 200 °C;

[0175] S8.3: Keep warm for 3 h;

[0176] S8.4: Heat up to 560 °C;

[0177] S8.5: Keep warm for 3 h;

[0178] S8.6: Heat up to 820 °C;

[0179] S8.7: Keep warm for 4 h;

[0180] S8.8: The sintering temperature is raised to 1082 °C and held for 7 hours;

[0181] S9: After sintering is completed, high-purity inert gas is filled in for cooling to below 100 °C;

[0182] S9.1: After going through a two-stage aging treatment process of holding at 900 °C for 2 - 3 hours and 500 °C for 3 - 6 hours, high-purity inert gas is filled in for cooling to below 100 °C;

[0183] S10: Take the central part of the sintered magnet, and use the pulse infrared absorption method to test the nitrogen and oxygen content in the blank, and use the high-frequency - infrared absorption method to test the carbon content in the blank;

[0184] S11: Take the sintered magnet and process it into a thin slice of 10 mm × 10 mm × 5 mm, and carry out grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.62 wt%;

[0185] S12: Use a NIM62000 type magnetic tester as the test equipment to test the magnetic properties before and after diffusion.

[0186] Example 2.1: The ingot formula is: (PrNd)28.5%Gd2.5%B0.95%Ti0.2%(Al + Cu + Ga)0.5%Co0.8%, and the rest is Fe.

[0187] The steps are as follows:

[0188] S1: Mix the neodymium iron boron raw materials in proportion;

[0189] S2: Melt the neodymium iron boron raw materials into an alloy liquid;

[0190] S3: Cast the alloy liquid into an ingot;

[0191] S4: Grind the ingot into powder, put it into a tank with inert gas protection, and stir well;

[0192] S4.1: Add a powder modifier, with an addition ratio of 0.08 wt%, and stir well;

[0193] S5: Press and orient the powder blank;

[0194] S5.1: Spray a mold release agent during the molding process, with a weight ratio of 0.075 wt%;

[0195] S6: Adopt vacuum packaging;

[0196] S7: Carry out hydrostatic isostatic pressing;

[0197] S8: Carry out sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating form;

[0198] S8.1: Start heating from room temperature;

[0199] S8.2: Heat up to 200 °C;

[0200] S8.3: Keep the temperature for 2 h;

[0201] S8.3.1: Fill with inert gas, filling pressure 0.05 MPa;

[0202] S8.3.2: After maintaining for 30 min, evacuate;

[0203] S8.3.3: Maintain for 30 min under vacuum;

[0204] S8.3.4: Repeat steps S8.3.1 - S8.3.3 once more;

[0205] S8.4: Heat up to 560 °C;

[0206] S8.5: Keep the temperature for 2 h;

[0207] S8.5.1: Fill with inert gas, filling pressure 0.05 MPa;

[0208] S8.5.2: After maintaining for 30 min, evacuate;

[0209] S8.5.3: Maintain for 30 min under vacuum;

[0210] S8.5.4: Repeat steps S8.5.1 - S8.5.3 once more;

[0211] S8.6: Heat up to 820 °C;

[0212] S8.7: Keep the temperature for 3 h;

[0213] S8.7.1: Fill with inert gas, filling pressure 0.05 MPa;

[0214] S8.7.2: After maintaining for 30 min, evacuate;

[0215] S8.7.3: Maintain for 30 min under vacuum;

[0216] S8.7.4: Repeat steps S8.7.1 - S8.7.3 twice;

[0217] S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, raise the sintering temperature to 1076 °C, keep the temperature for 5 h;

[0218] S9: After completing sintering, fill with high-purity inert gas and cool to below 100 °C;

[0219] S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C;

[0220] S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method;

[0221] S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.56wt%;

[0222] S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0223] Example 2.2: The casting formula is: (PrNd) 28.5% Gd 2.5% B 0.95% Ti 0.2% (Al + Cu + Ga) 0.5% Co 0.8%, and the rest is Fe.

[0224] The steps are as follows:

[0225] S1: Mix NdFeB raw materials in proportion;

[0226] S2: Smelting the NdFeB raw materials into alloy liquid;

[0227] S3: Casting the alloy liquid into casting sheets;

[0228] S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly;

[0229] S4.1: Add powder modifier at a ratio of 0.08wt% and stir thoroughly;

[0230] S5: Pressing the powder into a green compact and orienting the green compact;

[0231] S5.1: During the molding process, the mold release agent is sprayed in, with a weight ratio of 0.075wt%;

[0232] S6: vacuum packaging;

[0233] S7: performing water isostatic pressing;

[0234] S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form;

[0235] S8.1: Start heating from room temperature;

[0236] S8.2: Raise the temperature to 200°C;

[0237] S8.3: Insulate for 3 h;

[0238] S8.3.1: Fill with inert gas, filling pressure 0.05 MPa;

[0239] S8.3.2: After maintaining for 30 min, evacuate;

[0240] S8.3.3: Maintain in a vacuum state for 30 min;

[0241] S8.3.4: Repeat steps S8.3.1 - S8.3.3 two more times;

[0242] S8.4: Heat up to 560 °C;

[0243] S8.5: Insulate for 3 h;

[0244] S8.5.1: Fill with inert gas, filling pressure 0.05 MPa;

[0245] S8.5.2: After maintaining for 30 min, evacuate;

[0246] S8.5.3: Maintain in a vacuum state for 30 min;

[0247] S8.5.4: Repeat steps S8.5.1 - S8.5.3 two more times;

[0248] S8.6: Heat up to 820 °C;

[0249] S8.7: Insulate for 4 h;

[0250] S8.7.1: Fill with inert gas, filling pressure 0.05 MPa;

[0251] S8.7.2: After maintaining for 30 min, evacuate;

[0252] S8.7.3: Maintain in a vacuum state for 30 min;

[0253] S8.7.4: Repeat steps S8.7.1 - S8.7.3 three more times;

[0254] S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, raise the sintering temperature to 1076 °C, and insulate for 5 hours;

[0255] S9: After completion of sintering, fill with high-purity inert gas and cool to below 100 °C;

[0256] S9.1: Then undergo a two-stage aging treatment process of insulating at 900 °C for 2 - 3 hours and at 500 °C for 3 - 6 hours, and fill with high-purity inert gas and cool to below 100 °C;

[0257] S10: Take the central part of the sintered magnet, test the nitrogen and oxygen contents in the blank using the pulsed infrared absorption method, and test the carbon content in the blank using the high-frequency infrared absorption method;

[0258] S11: Process the sintered magnet into a thin slice of 10 mm×10 mm×5 mm, and perform grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.56 wt%;

[0259] S12: Use a NIM62000 magnetic tester as the test equipment to test the magnetic properties before and after diffusion.

[0260] Comparative Example 2: The ingot casting formula is: (PrNd)28.5%Gd2.5%B0.95%Ti0.2%(Al + Cu + Ga)0.5%Co0.8%, and the rest is Fe.

[0261] The steps are as follows:

[0262] S1: Mix the neodymium iron boron raw materials in proportion;

[0263] S2: Melt the neodymium iron boron raw materials into an alloy liquid;

[0264] S3: Cast the alloy liquid into an ingot;

[0265] S4: Grind the ingot into powder, put it into a tank with inert gas protection, and stir well;

[0266] S4.1: Add a powder modifier with an addition ratio of 0.08 wt%, and stir well;

[0267] S5: Press and orient the powder blank;

[0268] S5.1: Spray a release agent during the forming process, with a weight ratio of 0.075 wt%;

[0269] S6: Adopt vacuum packaging;

[0270] S7: Perform hydrostatic isostatic pressing;

[0271] S8: Perform sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating form;

[0272] S8.1: Start heating from room temperature;

[0273] S8.2: Heat up to 200 °C;

[0274] S8.3: Keep warm for 3 h;

[0275] S8.4: Heat up to 560 °C;

[0276] S8.5: Keep warm for 3 h;

[0277] S8.6: Heat up to 820 °C;

[0278] S8.7: Keep the temperature for 4 h;

[0279] S8.8: Raise the sintering temperature to 1076 °C and keep the temperature for 5 hours;

[0280] S9: After sintering is completed, fill with high-purity inert gas and cool to below 100 °C;

[0281] S9.1: Then, carry out a two-stage aging treatment process of keeping the temperature at 900 °C for 2 - 3 hours and 500 °C for 3 - 6 hours, and fill with high-purity inert gas and cool to below 100 °C;

[0282] S10: Take the central part of the sintered magnet, and use the pulse infrared absorption method to test the nitrogen and oxygen contents in the blank, and use the high-frequency - infrared absorption method to test the carbon content in the blank;

[0283] S11: Process the sintered magnet into a thin sheet of 10 mm x 10 mm x 5 mm, and carry out grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.56 wt%;

[0284] S12: Use the NIM62000 magnetic tester as the test equipment to test the magnetic properties before and after diffusion.

[0285] Example 3.1: The casting sheet formula is: (PrNd) 28.8% (Dy + Gd) 2.1% B 0.95% Ti 0.2% (Al + Cu + Ga) 1.0% Co 0.5%, and the rest is Fe.

[0286] The steps are as follows:

[0287] S1: Mix the neodymium iron boron raw materials in proportion;

[0288] S2: Melt the neodymium iron boron raw materials into an alloy liquid;

[0289] S3: Cast the alloy liquid into casting sheets;

[0290] S4: Grind the casting sheets into powder, put them into a tank with inert gas protection, and stir well;

[0291] S4.1: Add a powder modifier with an addition ratio of 0.08 wt%, and stir well;

[0292] S5: Press and orient the powder blank;

[0293] S5.1: Spray a mold release agent during the forming process, with a weight ratio of 0.075 wt%;

[0294] S6: Adopt vacuum packaging;

[0295] S7: Perform hydrostatic isostatic pressing;

[0296] S8: Perform sintering and film stripping, and the sintering adopts a multi-stage heat preservation and heating form;

[0297] S8.1: Heat up from room temperature;

[0298] S8.2: Heat up to 200 °C;

[0299] S8.3: Keep warm for 2 h;

[0300] S8.3.1: Fill with inert gas, and the filling pressure is 0.05 MPa;

[0301] S8.3.2: After maintaining for 30 min, evacuate;

[0302] S8.3.3: Keep in a vacuum state for 30 min;

[0303] S8.3.4: Repeat the steps of S8.3.1 - S8.3.3 once again;

[0304] S8.4: Heat up to 560 °C;

[0305] S8.5: Keep warm for 2 h;

[0306] S8.5.1: Fill with inert gas, and the filling pressure is 0.05 MPa;

[0307] S8.5.2: After maintaining for 30 min, evacuate;

[0308] S8.5.3: Keep in a vacuum state for 30 min;

[0309] S8.5.4: Repeat the steps of S8.5.1 - S8.5.3 once again;

[0310] S8.6: Heat up to 820 °C;

[0311] S8.7: Keep warm for 3 h;

[0312] S8.7.1: Fill with inert gas, and the filling pressure is 0.05 MPa;

[0313] S8.7.2: After maintaining for 30 min, evacuate;

[0314] S8.7.3: Keep in a vacuum state for 30 min;

[0315] S8.7.4: Repeat the steps of S8.7.1 - S8.7.3 twice;

[0316] S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature was raised to 1073°C and kept at this temperature for 5 hours;

[0317] S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C;

[0318] S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C;

[0319] S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method;

[0320] S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.65wt%;

[0321] S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0322] Example 3.2: The casting formula is: (PrNd) 28.8% (Dy+Gd) 2.1% B 0.95% Ti 0.2% (Al+Cu+Ga) 1.0% Co 0.5%, and the rest is Fe.

[0323] The steps are as follows:

[0324] S1: Mix NdFeB raw materials in proportion;

[0325] S2: Smelting the NdFeB raw materials into alloy liquid;

[0326] S3: Casting the alloy liquid into casting sheets;

[0327] S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly;

[0328] S4.1: Add powder modifier at a ratio of 0.08wt% and stir thoroughly;

[0329] S5: Pressing the powder into a green compact and orienting the green compact;

[0330] S5.1: During the molding process, the mold release agent is sprayed in, with a weight ratio of 0.075wt%;

[0331] S6: vacuum packaging;

[0332] S7: performing water isostatic pressing;

[0333] S8: Conduct sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating method.

[0334] S8.1: Heat up from room temperature.

[0335] S8.2: Heat up to 200 °C.

[0336] S8.3: Keep the temperature for 3 h.

[0337] S8.3.1: Fill with inert gas, and the filling pressure is 0.05 MPa.

[0338] S8.3.2: After maintaining for 30 min, evacuate the vacuum.

[0339] S8.3.3: Keep the vacuum for 30 min.

[0340] S8.3.4: Repeat the steps of S8.3.1 - S8.3.3 twice.

[0341] S8.4: Heat up to 560 °C.

[0342] S8.5: Keep the temperature for 3 h.

[0343] S8.5.1: Fill with inert gas, and the filling pressure is 0.05 MPa.

[0344] S8.5.2: After maintaining for 30 min, evacuate the vacuum.

[0345] S8.5.3: Keep the vacuum for 30 min.

[0346] S8.5.4: Repeat the steps of S8.5.1 - S8.5.3 twice.

[0347] S8.6: Heat up to 820 °C.

[0348] S8.7: Keep the temperature for 4 h.

[0349] S8.7.1: Fill with inert gas, and the filling pressure is 0.05 MPa.

[0350] S8.7.2: After maintaining for 30 min, evacuate the vacuum.

[0351] S8.7.3: Keep the vacuum for 30 min.

[0352] S8.7.4: Repeat the steps of S8.7.1 - S8.7.3 three times.

[0353] S8.8: Evacuate the vacuum to a vacuum degree less than 10 -2 Pa, raise the sintering temperature to 1073 °C, and keep the temperature for 5 h.

[0354] S9: After sintering is completed, charge with high-purity inert gas and cool to below 100 °C;

[0355] S9.1: Then, through a two-stage aging treatment process of holding at 900 °C for 2 - 3 hours and 500 °C for 3 - 6 hours, charge with high-purity inert gas and cool to below 100 °C;

[0356] S10: Take the central part of the sintered magnet, use the pulse infrared absorption method to test the nitrogen and oxygen content in the blank, and use the high-frequency - infrared absorption method to test the carbon content in the blank;

[0357] S11: Take the sintered magnet and process it into a thin slice of 10 mm × 10 mm × 5 mm, and carry out grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.65 wt%;

[0358] S12: Use a NIM62000-type magnetic tester as the test equipment to test the magnetic properties before and after diffusion.

[0359] Comparative Example 3: The casting sheet formula is: (PrNd) 28.8% (Dy + Gd) 2.1% B 0.95% Ti 0.2% (Al + Cu + Ga) 1.0% Co 0.5%, and the rest is Fe.

[0360] The steps are as follows:

[0361] S1: Mix neodymium-iron-boron raw materials in proportion;

[0362] S2: Melt the neodymium-iron-boron raw materials into an alloy liquid;

[0363] S3: Cast the alloy liquid into casting sheets;

[0364] S4: Grind the casting sheets into powder, put them into a tank with inert gas protection, and stir well;

[0365] S4.1: Add a powder modifier, with an addition ratio of 0.08 wt%, and stir well;

[0366] S5: Press and orient the powder blank;

[0367] S5.1: Spray a release agent during the forming process, with a weight ratio of 0.075 wt%;

[0368] S6: Adopt vacuum packaging;

[0369] S7: Carry out hydrostatic isostatic pressing;

[0370] S8: Carry out sintering and film stripping. The sintering adopts a multi-stage heat preservation and heating form;

[0371] S8.1: Start heating from room temperature;

[0372] S8.2: Heat up to 200 °C;

[0373] S8.3: Keep the temperature for 3 h;

[0374] S8.4: Heat up to 560 °C;

[0375] S8.5: Keep the temperature for 3 h;

[0376] S8.6: Heat up to 820 °C;

[0377] S8.7: Keep the temperature for 4 h;

[0378] S8.8: Raise the sintering temperature to 1073 °C and keep the temperature for 5 hours;

[0379] S9: After sintering is completed, fill with high-purity inert gas and cool to below 100 °C;

[0380] S9.1: Then, carry out a two-stage aging treatment process of keeping the temperature at 900 °C for 2 - 3 hours and 500 °C for 3 - 6 hours, and fill with high-purity inert gas to cool to below 100 °C;

[0381] S10: Take the central part of the sintered magnet, and use the pulse infrared absorption method to test the nitrogen and oxygen contents in the blank, and use the high-frequency - infrared absorption method to test the carbon content in the blank;

[0382] S11: Take the sintered magnet and process it into a thin sheet of 10 mm x 10 mm x 5 mm, and carry out grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.65 wt%;

[0383] S12: Use a NIM62000-type magnetic tester as the test equipment to test the magnetic properties before and after diffusion.

[0384] The above pulse infrared absorption method and high-frequency - infrared absorption method are both conventional test methods.

[0385] As Figure 1 shown, the figure is the sintering curve and the sintering equipment pressure change curve in the sintering equipment of Example 1.2, Example 2.2, and Example 3.2.

[0386] Table 1 Carbon and oxygen contents in the central part of the magnet blanks in each example and comparative example

[0387]

[0388] Table 2 Magnetic properties before and after diffusion and the increase in coercivity in each example and comparative example

[0389]

[0390] Magnets processed by a neodymium iron boron sintering method that contributes to decarbonization have the following improvements:

[0391] 1. As can be seen from Table 1, among neodymium iron boron magnets of the same type, the carbon and oxygen contents of magnets that have undergone repeated charging with inert gas and vacuum pumping will decrease significantly.

[0392] 2. As can be seen from Table 2, among neodymium iron boron magnets of the same type, the H CJ has been improved, and the magnetic properties of the magnet are better.

[0393] By adopting multi-stage heating and heat preservation platform during sintering, and introducing and extracting inert gas during heat preservation to form an alternating heat preservation sintering with inert gas pressure difference, the internal carbon content of the blank can be effectively reduced, thereby reducing the blockage of grain boundary diffusion by carbon elements, increasing the diffusion range of grain boundary diffusion, and thus improving the magnetic properties of the neodymium iron boron magnet.

[0394] The above is only an illustration of the best embodiment of the present invention, but it should not be construed as a limitation on the claims. The present invention is not limited to the above embodiments, and its specific structure allows for changes. All changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

Claims

1. A method for sintering NdFeB that facilitates decarburization, characterized in that: The formula of NdFeB magnet is (PrNd)30%B0.94%Ti0.2%(Al+Cu+Ga)0.35%Co1%, the rest is Fe, Or (PrNd) 28.5% Gd 2.5% B 0.95% Ti 0.2% (Al + Cu + Ga) 0.5% Co 0.8%, the rest is Fe, Or (PrNd) 28.8% (Dy + Gd) 2.1% B 0.95% Ti 0.2% (Al + Cu + Ga) 1.0% Co 0.5%, the rest is Fe, the above percentages are mass percentages, a multi-stage heating and insulation platform is used during sintering, and inert gas is introduced and extracted during insulation to form an inert gas pressure difference for alternate insulation sintering, thereby reducing the carbon content inside the blank, the steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank protected by inert gas, and stir them thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed. The sintering adopts a multi-stage heat preservation and temperature rise form, and inert gas is introduced and extracted during the heat preservation to form an inert gas pressure difference for alternating heat preservation and sintering; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 2 hours; S8.3.1: Fill with inert gas at a pressure of 0.05 MPa; S8.3.2: After holding for 30 min, apply vacuum; S8.3.3: Maintain under vacuum for 30 min; S8.3.4: Repeat steps S8.3.1-S8.3.3 once more; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 2 hours; S8.5.1: Fill with inert gas at a pressure of 0.05 MPa; S8.5.2: After holding for 30 min, apply vacuum; S8.5.3: Maintain under vacuum for 30 min; S8.5.4: Repeat steps S8.5.1-S8.5.3 once more; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 3 hours; S8.7.1: Fill with inert gas at a pressure of 0.05 MPa; S8.7.2: After holding for 30 min, apply vacuum; S8.7.3: Maintain under vacuum for 30 min; S8.7.4: Repeat steps S8.7.1-S8.7.3 two more times; S9: After sintering, cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: processing the sintered magnet into thin sheets and performing grain boundary diffusion; S12: Use a magnetic tester to test the magnetic properties before and after diffusion.

2. A NdFeB sintering method that helps decarburization according to claim 1, characterized in that: After step S8.7, the method further includes the following steps: S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature is raised to 1050±50℃ and the insulation time is 4 to 15 hours.

3. A NdFeB sintering method that helps decarburization according to claim 2, characterized in that: In step S9, after sintering is completed, high-purity inert gas is filled in to cool to below 100°C.

4. A NdFeB sintering method that helps decarburization according to claim 1, characterized in that: After step S9, the method further includes step S9.1: performing aging treatment on the sintered magnet.

5. A NdFeB sintering method that helps decarburization according to claim 1, characterized in that: In step S4, the step S4.1 is included: adding a powder modifier in a proportion of 0.05wt%-0.5wt% and stirring the mixture thoroughly.

6. A NdFeB sintering method that helps decarburization according to claim 1, characterized in that: In step S5, the step S5.1 is included: spraying a release agent during the orientation molding process.

Citation Information

Patent Citations

  • Sintering technology of NdFeB (neodymium iron boron) magnet

    CN103357872A

  • Low-cost high-cerium neodymium-iron-boron diffusion magnet and preparation method and application thereof

    CN119673646A